Establishing a Veterinary Anatomy core syllabus through a modified Delphi process. - Gummery, Erica; Singh, Miren; Channon, Sarah B (Wiley, 2023)
Anatomy forms a key component of veterinary curricula, but, in the context of an evolving profession, curricula are adapting and changing accordingly. There is a lack of guidance for educators regarding the levels of anatomical knowledge required for a graduate to be considered safe, or competent. A formal review of veterinary anatomy learning outcomes (LOs) is therefore timely to support curriculum development in this rapidly evolving field. This study aimed to create a set of learning outcomes which reflect the recommended core requirements for a new graduate veterinarian. A consensus approach using a modified Delphi method was used. The Delphi panel consisted of 23 experienced and active veterinary anatomy educators from veterinary schools within the UK and Ireland. The process had four stages: 1) Research team review, pre-screening and modification of a list of existing LOs (adapted from the Core Regional Anatomy Syllabus) which then formed the initial set of outcomes sent for review; 2) Delphi round one; 3) Delphi Round two; 4) Post-Delphi final screening and review. Qualitative data outlining the rationale for modification and rejection of LOs were analysed via content analysis. 167 LOs were initially presented to the Delphi panel in Round 1. 64 of those were accepted, 79 recommended for modification, and 23 rejected. 122 learning outcomes were presented to the Delphi panel in Round two. Of these, 86 outcomes were accepted, 10 modified, and 26 rejected. 160 LOs were ultimately accepted and form the Veterinary Anatomy Core Syllabus. Key themes arising from analysis include the removal of unnecessary detail and increased focus on the relevance of competencies required of a new veterinary graduate. The syllabus presented may be used by curriculum planners, teachers, and students within veterinary education worldwide.
1
Keywords: Pedagogy; 31 Education; curriculum; anatomy knowledge; veterinarian; consensus survey